Assessing the Relevance of Education for SelfReliance in Public Secondary Schools in Meru District Council in Arusha-Tanzania - Jerome, Gabriel; Mkulu, Demetria Gerold (International Journal of Humanities and Education Development (IJHED), 2020)
Education for Self-Reliance has been in practice in Tanzania for several years since 1967. The country made reforms in various education policies and programs to ensure that students in secondary schools are provided with Education for Self-Reliance (ESR) to realize national education objectives. This study sought to examine the relevance of ESR in secondary schools on helping students to have independent living after graduation. The study was guided by the following objectives, to assess the relevance of Education for Self-Reliance and to ascertain the subjects empowering students in Self-Reliance in secondary schools. The study adopted the human capital theory developed in 1776 and adopted by Theodor Schultz in the field of education in 1969. The researcher used a mixed research approach and convergent parallel research design to collate data. A sample size of 192 informants was used to provide data in quantitative and qualitative terms. Quantitative data were analyzed with the support of SPSS program version 20, while qualitative data was analyzed through coding, categories and themes. Content and face validity of the instrument were observed and reliability tested in split-half system to obtain 0.80 correlation coefficient which showed the research instruments were valid and reliable. The findings postulated that ESR is relevant as it helps students to alleviate poverty, create employment, increase confidence, promote students’ knowledge and skills and free them from crimes and immoralities after graduation. Also, the researcher found that physical education, music, fine arts, commerce, business studies, computer studies and agriculture are very crucial subjects in empowering students in Self-Reliance, however, teachers do not teach these Self-Reliance subjects in public secondary schools. Therefore students are completed secondary schools with inadequate skills for Self[1]Reliance which leads to unemployment, engaging in crimes and failure to seize opportunities around. The researcher further recommended that the Ministry of Education Science and Technology to contrive an educational policy framework to emphasize the teaching of ESR subjects in secondary schools. Also, training and retraining of teachers on Self-Reliance can be an effective way to provide ESR in public secondary schools.